Kinematic interaction between stratigraphically discrete salt layers; the structural evolution of the Corrib gas field, offshore NW Ireland. (November 2021) - O'Sullivan, Conor; Childs, Conrad
Abstract: The kinematic interaction of thin salt layers during basin evolution has received little attention to date, despite there being several basins which contain multiple thin salt layers across NW Europe. This study utilises high-quality 3D seismic reflection data coupled with borehole data to investigate the evolution of the structure containing the Corrib gas field which is composed of two distinct salt structures. Located in the Slyne Basin offshore NW Ireland, the structure consists of a NE-SW oriented Permian salt anticline which folds the overlying Mesozoic stratigraphy. Upper Triassic salt acts as a second mechanical detachment and forms an elongate salt roller parallel to the crest of the Permian salt anticline. The Upper Triassic salt roller forms the footwall of a listric fault which downthrows the anticlinal crest of the folded Jurassic section to the SE. The Permian salt anticline began rising during the Late Triassic and Early Jurassic driven by low-strain regional extension. During the main phase of rifting, a combination of basement tilting, gravity gliding, and salt welding resulted in a steep increase in the amplitude of the Permian salt anticline. The relief on the salt-cored fold resulted in gravity gliding on the Triassic salt, forming the parallel salt roller and listric fault. The throw distribution on the listric fault is driven by the combined mechanisms of gravity sliding on the Triassic salt and by inflation of Triassic salt in the footwall of the fault. The listric fault is reactivated post-rift, suggesting modification of the Permian and Triassic salt structures. This study improves the understanding of the kinematic interaction of thin salt layers during syn-rift and post-rift deformation, with implications for hydrocarbon exploration on the Irish Atlantic margin and further afield. Highlights: The key components of the Corrib structure are a salt anticline, a salt wall and complex faulted and folded overburden. High-strain extensional tectonic forces and halokinesis are the primary drivers for the evolution of the Corrib structure. The NE-SW oriented Corrib fault in the Jurassic overburden formed by linkage of left-stepping ENE-WSW fault segments. Deeper salt layers influence the location, orientation, and size of halokinetic structures in shallower layers of salt.